Measuring Good Architecture: Long life, loose fit, low energy - Langston, Craig (European Journal of Sustainable Development, 2014)
Good architecture is something that we all seek, but which is difficult to define. Sir Alexander John Gordon, in his role as President of the Royal Institute of British Architects, defined ‘good architecture’ in 1972 as buildings that exhibit ‘long life, loose fit and low energy’. These characteristics, nicknamed by Gordon as the 3L Principle, are measurable. Furthermore, life cycle cost (LCC) provides a method for accessing the economic contribution or burden created by buildings to the society they aim to serve. Yet there is no research available to investigate the connection, if any, between 3L and LCC. It might be hypothesised that buildings with a high 3L index have a low LCC profile. If this is true, then LCC may be able to be used to assess ‘good architecture’.This paper uses a case study methodology to assess the durability, adaptability and sustainability of 22 projects that have won architectural design awards. The 3L criteria can bemeasured and compared with average LCC per square metre using a long time horizon. The research is significant in that it tests a process to objectively assess what is commonly intangible and to determine if LCC is a suitable predictor of ‘good architecture’. Keywords: Sustainable urbanism, architecture, built environment